Novel circular RNA circ-0002727 regulates miR-144-3p/KIF14 pathway to promote lung adenocarcinoma progression - Li, Yang; Hong, Xiu; Zhai, Jingfang; Liu, Ying; Li, Rui; Wang, Xiuli; Zhang, Youwei; Lv, Qian (Frontiers in Cell and Developmental Biology, 2023)
Objective: Circular RNAs (circRNAs) have been shown to participate in various cancers via sponging miRNAs (microRNAs). However, their role in lung adenocarcinoma (LUAD) remains elusive.The transcriptome data and corresponding clinical information of lung adenocarcinoma samples were extracted from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database. Differentially expressed circRNAs (DEcircRNAs), differentially expressed miRNAs (DEmiRNAs), and differentially expressed genes (DEgenes) were identified and further used to constructed a circRNA-associated competing endogenous RNA (ceRNA) network. Real-Time qPCR analysis was conducted to examine gene expression at transcriptional level. The regulatory mechanisms of circRNA-miRNA-gene were validated by dual-luciferase reporter array and RNA pull-down assay. Cell growth, migration and invasion were evaluated by CCK-8 assay, colony formation assay and transwell assay, respectively.Results: Based on public microarray data, we systematically constructed a circRNA-associated ceRNA network including 11 DEcircRNAs, 8 DEmiRNAs and 49 DEgenes. Among the ceRNA network, we found that circ-0002727 was a key regulatory and was further confirmed to be upregulated in LUAD cancer cells. Subsequently, we found that silencing of circ-0002727 significantly suppressed the LUAD cell proliferation, migration and invasion in vitro.Mechanistically, we showed that circ-0002727 could competitively bind miR-144-3p to enhance the KIF14 expression in LUAD cells. Rescue assays indicated that circ-0002727 could regulate LUAD cell proliferation through modulating miR-144-3p/KIF14 pathway. Besides, KIF14 expression level This is a provisional file, not the final typeset article was positively correlated with TNM stage and metastasis, and patients with high KIF14 expression suffered poor prognosis.Taken together, our study revealed that circ-0002727 could act as a ceRNA to regulate LUAD progression via modulating miR-144-3p/KIF14 pathway, providing a potential therapeutic target for LUAD.